Determination of specific heat capacity of bio-fibre earth mortars stabilised at different relative humidities using Differential Scanning Calorimetry. (September 2021) - Romano, A.; Grammatikos, S.; Riley, M.; Bras, A.
Abstract: Understanding the relationship that earth-based mortars have with both water and temperature is imperative to optimise moisture buffering properties. Specific Heat Capacity (Cp ) is a key factor to understand the benefits in terms of thermal mass and latent heat. This paper presents the results of bio-based earth mortars (with fibres consisting of two varieties of sheep wool: Wool 1 (W1), Wool 2(W2) and Saw Mill Residue (SMR)) stabilised at 53% and 75% Relative Humidity (RH). Differential Scanning Calorimetry (DSC) according to ISO 11357–4 was used to calculate Cp of the aforementioned mortars. The temperature range of this experiment was that of 0–50 °C with a particular focus on values at 20 °C as this best represented a suitable indoor temperature. From these experiments, the results demonstrate that when stabilised at different RH, the difference in Cp was bio-fibre dependant and had a range between 0.71– 1.01 kJ/kg.K at 53% RH and 0.85–1.14 kJ/kg.K at 75% RH. These differences could potentially be attributed to the materials ability to readily accept water molecules. This emphasised that incorporating bio-fibres to a plain mixture (PL) can increase the Cp by up to 60%; significantly improving the thermal inertia of the building material. By reducing this temperature differential, it will reduce the heating requirements of a building which as consequential carbon reduction and thermal comfort benefits. Overall, SMR has the largest Cp for 75% at 20 °C was 1.141 kJ/kg.K, therefore specifically, this fibre would be the most effective to implement within a building. It also demonstrates the differences of the samples adsorption and absorption of water in differing hygrothermal environments. Highlights: Bio-based earth mortars with fibres consisting of two varieties of sheep wool: Wool 1 (W1), Wool 2(W2) and Saw Mill Residue (SMR)) were stabilised at 53% and 75% Relative Humidity (RH). Differential Scanning Calorimetry (DSC) was utilised according to ISO 11357–4 to calculate specific heat capacity (Cp) of mortars at the differing RHs. All bio-fibre mix designs had larger Cp by comparison to its plain counterpart. SMR has the largest Cp for 75% at 20 °C was 1.141 kJ/kg.K, this fibre is the most effective to implement within a building.